ANALISIS YURIDIS TERHADAP SANKSI HUKUM KEPADA ANAK DIBAWAH UMUR YANG DIMANFAATKAN OLEH BANDAR NARKOTIKA SEBAGAI KURIR NARKOTIKA - Gunawan Marthin Panjaitan; Alpi Sahari (JURNAL DOKTRIN REVIEW, 2022)
Narcotics crime cases that are happening today, dealers in narcotics trading involve minors as narcotics couriers whose job is to deliver or buy and sell narcotics. Involving children who are included to facilitate narcotics dealers in conducting transactions to deceive law enforcement officers. The factors that cause children to become drug couriers are the lack of supervision from parents; environmental factor; economic factors. Legal protection for children who are used as couriers in narcotics crimes, then based on Article 5 of Law No. 11 of 2012 concerning SPPA, a diversion process must be pursued with a restorative justice approach, starting from the process of investigation, prosecution to examination in court. criminal sanctions against children who become narcotics couriers, criminal sanctions are imposed or action is imposed, related to criminal sanctions Article 81 of Law no. 11 of 2012 concerning SPPA, the criminal sanction of imprisonment is (half) of the maximum threat of imprisonment for adults. Related actions are: returning to parents or guardians, treatment in mental hospitals, treatment at LPKS, obligations to attend education or training, repairs due to criminal acts (restorative justice).